An Analysis of Some Factors Affecting Employee Performance at Bank NTB Syariah Praya Branch - Agus Salihin; Syamsul Sukmono Edy (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study aims to analyze the factors that affect the performance of employees at Bank NTB Syariah Praya Branch. This research is a quantitative study using primary data obtained from distributing questionnaires. The research sample consisted of 30 respondents consisting of NTB Syariah bank employees at the Praya branch. Methods of data analysis in this study using multiple linear regression with the help of SPSS software. The results showed that partially and simultaneously the variables of organizational culture, motivation and compensation have a significant positive effect on the employee performance of Bank NTB Syariah Praya Branch. Then the coefficient of determination was 81.1%. This means that the independent variable is able to explain the dependent variable by 81.1%.Penelitian ini bertujuan untuk menganalisis faktor yang mempengaruhiikinerja karyawan pada Bank NTB Syariah Cabang Praya.Penelitian ini termasuk penelitiannkuantitatif yang menggunakan data primer yang diperoleh dari penyebarannkuesioner. Sampel penelitiannsebanyak 30 responden yang terdiri dari karyawan bank NTB Syariah cabang praya. Metode analisis data dalammpenelitian ini menggunakan regresi linierberganda dengan bantuan software SPSS.Hasil penelitiannmenunjukkan bahwa secara parsial dan simultan variabel budaya organisasi, motivasi dan kompensasi berpengaruh positif signifikan terhadap kinerja karyawan Bank NTB Syariah Cabang Praya. Kemudian nilai koefisien determinasi sebesar 81,1%. Hal ini berarti bahwa variabel bebas mampuumenjelaskan variabellterikat sebesar 81,1%.